2001
DOI: 10.4049/jimmunol.166.10.6444
|View full text |Cite
|
Sign up to set email alerts
|

Complement Component C3 Is Not Required for Full Expression of Immune Complex Glomerulonephritis in MRL/lprMice

Abstract: Complement activation and tissue deposition of complement fragments occur during disease progression in lupus nephritis. Genetic deficiency of some complement components (e.g., Factor B) and infusion of complement inhibitors (e.g., Crry, anti-C5 Ab) protect against inflammatory renal disease. Paradoxically, genetic deficiencies of early components of the classical complement pathway (e.g., C1q, C4, and C2) are associated with an increased incidence of lupus in humans and lupus-like disease in murine knockout s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 58 publications
7
96
0
Order By: Relevance
“…Another study showed that homozygous deficiencies of C4 and CD21/CD35 (CR1/CR2) accelerated disease in C57BL/6.lpr/lpr mice, although paradoxically C3-deficient C57BL/6.lpr/lpr mice behaved in a similar fashion as controls (21). Furthermore, C3 deficiency in MRL/Mp-lpr/lpr mice has been shown to have minimal effects on disease expression (22). In light of all these observations, it can be speculated that the underlying explanation for these apparently conflicting reports may lie in the nature of the genetic background of the mice used for these various analyses or may reflect the complexity of the multiple biological roles of the complement system in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that homozygous deficiencies of C4 and CD21/CD35 (CR1/CR2) accelerated disease in C57BL/6.lpr/lpr mice, although paradoxically C3-deficient C57BL/6.lpr/lpr mice behaved in a similar fashion as controls (21). Furthermore, C3 deficiency in MRL/Mp-lpr/lpr mice has been shown to have minimal effects on disease expression (22). In light of all these observations, it can be speculated that the underlying explanation for these apparently conflicting reports may lie in the nature of the genetic background of the mice used for these various analyses or may reflect the complexity of the multiple biological roles of the complement system in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…36,[38][39][40][41] To assess the effect of HSP90 inhibition on renal pathology, kidneys were taken from MRL/lpr mice at 18 weeks of age after being treated with 17-DMAG. For PAS staining, kidneys were formalin-fixed and sections were stained by the PAS method.…”
Section: Hsp90 Inhibition Reduced Inflammatory Mediator Production Inmentioning
confidence: 99%
“…[32][33][34][35][36][37] Renal histological markers of glomerular lesions and glomerular deposition of IgG and C3 can also indicate disease. 36,[38][39][40][41] Splenocyte populations are often altered in autoimmune mice including differences in T-cell subtypes (including T regulatory cells (T REG )) and also alterations in B-cell subtypes. 36,37,42,43 HSP90 has been implicated in studies investigating similar autoimmune diseases and it has been reported that T cells respond to extracellular HSP90 by increasing their anti-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Serum autoantibody levels against dsDNA and glomerular Ags (GA) were measured as described previously (27). For the anti-DNA ELISA, plates were coated overnight at 37°C with double-stranded calf thymus DNA (5 g/ml; Sigma-Aldrich) diluted in SSC buffer.…”
Section: Autoantibody Elisamentioning
confidence: 99%